ESG investment and risks: conceptualise the unexpected - Mohamed Yousop, Nur Liyana; Ab Razak, Nazrul Hisyam (UiTM Press, 2023)
Investors are integrating ESG factors into their decision-making processes to invest sustainably and gain competitive returns. The presence of risks from the recent past and the near future and the occurrence of a rare, unforeseeable, and economically significant event, known as a black swan event, hinder their ability to make sound investment decisions. In light of this, our study aims to develop a conceptual framework for the risk-return issue in ESG investments. The Southeast Asia region will be emphasised more due to its potential for future ESG investment growth and higher returns. Consequently, our investigation provides two possible frameworks to measure the relationship between ESG risks and ESG firms' stock returns in Southeast Asia. In the absence of ESG indices in the region, local ESG companies listed on stock markets have been suggested as a viable alternative.